Phytochemicals from Indian Ethnomedicines: Promising Prospects for the Management of Oxidative Stress and Cancer - Fatima, Nishat; Baqri, Syed Shabihe Raza; Alsulimani, Ahmad; Fagoonee, Sharmila; Slama, Petr; Kesari, Kavindra Kumar; Roychoudhury, Shubhadeep; Haque, Shafiul (Antioxidants (Basel, Switzerland), 2021)
Oxygen is indispensable for most organisms on the earth because of its role in respiration. However, it is also associated with several unwanted effects which may sometimes prove fatal in the long run. Such effects are more evident in cells exposed to strong oxidants containing reactive oxygen species (ROS). The adverse outcomes of oxidative metabolism are referred to as oxidative stress, which is a staple theme in contemporary medical research. Oxidative stress leads to plasma membrane disruption through lipid peroxidation and has several other deleterious effects. A large body of literature suggests the involvement of ROS in cancer, ageing, and several other health hazards of the modern world. Plant-based cures for these conditions are desperately sought after as supposedly safer alternatives to mainstream medicines. Phytochemicals, which constitute a diverse group of plant-based substances with varying roles in oxidative reactions of the body, are implicated in the treatment of cancer, aging, and all other ROS-induced anomalies. This review presents a summary of important phytochemicals extracted from medicinal plants which are a part of Indian ethnomedicine and Ayurveda and describes their possible therapeutic significance.
Keywords: cancer; oxidative stress; ROS; phytochemicals; ethnomedicine